A listener's stance-taking in mediation. Issue 2 (2nd October 2017) - Ingram, Matthew; Maxwell, Madeline
Abstract : This article analyses a highly acrimonious conflict mediation session between a previous romantic couple in order to illustrate how one listening disputant's embodied stances influence the trajectory of another disputant's unfolding narrative. For example, even without speaking, the listener's facial expression and postures serve to refuse the other speaker's participant framework. In order to unpack the complexity of this interaction, we drew on both conversation analytic and dialogic notions of stance. We found that to analyse embodied stances in our data requires an understanding of both the local sequential analysis of the unfolding orientations of the participants as embodied stances are being deployed, as well as the larger interactional patterns that occur across the entire mediation session. This case study illustrates the challenge, to mediators and researchers alike, posed by unequal access to the disputant's shared background knowledge.